2004
DOI: 10.1128/aac.48.7.2704-2707.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lysostaphin-Coated Catheters Eradicate Staphylococccus aureus Challenge and Block Surface Colonization

Abstract: Lysostaphin is an endopeptidase that kills Staphylococcus aureus, a predominant organism in catheterrelated infections. Lysostaphin-coated catheters prevented catheter colonization by several strains of S. aureus, and activity was maintained for at least 4 days. Prophylactic use of lysostaphin in catheters may help prevent the occurrence of catheter-related staphylococcal infections.Catheter-related infections continue to be a significant source of morbidity and mortality in patients requiring catheterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 17 publications
3
47
1
Order By: Relevance
“…These authors used a methodology similar to that reported here. One possible explanation is the difference in materials used in our studies and the studies of Shah et al (28). Ultrapro, a lightweight polypropylene macroporous mesh (with a Monocryl weave) containing an absorbable component of poliglecaprone, is different in density, weave, porosity (3 mm), and relative hydrophobicity.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…These authors used a methodology similar to that reported here. One possible explanation is the difference in materials used in our studies and the studies of Shah et al (28). Ultrapro, a lightweight polypropylene macroporous mesh (with a Monocryl weave) containing an absorbable component of poliglecaprone, is different in density, weave, porosity (3 mm), and relative hydrophobicity.…”
Section: Discussioncontrasting
confidence: 39%
“…The antimicrobial activity of the meshes is primarily due to the extremely low concentrations of lysostaphin leaching from the mesh surface into the supernatant. Interestingly, Shah et al observed that the antimicrobial activity of lysostaphin coated on two different plastic surfaces, polystyrene (well plates) and fluorinated ethylene-propylene (FEP) polymer, a Teflon-like material used in Angiocath catheters, was primarily due to immobilized but not leached enzyme (28). These authors used a methodology similar to that reported here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cotton rat model of S. aureus nasal colonization, lysostaphin was shown to be more effective than mupirocin, which is currently the main antibiotic used as a decolonizing agent . Another prophylactic use of lysostaphin might be prevention of catheter colonization by enzyme molecules coating their surface (Shah et al 2004 ).…”
Section: Lysostaphinmentioning
confidence: 99%
“…Its use as a therapeutic agent to prevent and treat S. aureus infections is not novel, as it has been shown to be an effective topical antimicrobial to control cutaneous infections and carriage of methicillin-resistant Staphylococcus aureus (MRSA) (53). In addition, lysostaphin has been used as a treatment for reducing S. aureus in blood and organs of infected mice (35) and infections of the rabbit eye caused by MRSA (17,18) as well as a means to reduce colonization by S. aureus when applied as a precoat to catheters (67). Lysostaphin has also been used to reduce S. aureus in the nasal passages of humans (25,36,55) and has actually been used to treat a staphylococcal abscess in a neutropenic patient (70).…”
mentioning
confidence: 99%